A parametric study on the effect of uniformly-induced curvature on the deformational capacity of steel onshore pipelines based on a novel material characterization procedure. (1st May 2021) - Ndubuaku, Onyekachi; Roger Cheng, J.J.; Martens, Michael; Adeeb, Samer
Highlights: A simple robust material model for stress–strain curve parameterization is defined. CLS equations are derived according to two material curve shape classifications (YPT and RHT). Functional relationships between constitutive parameters and CLS are graphically deciphered. CLS equation is derived by direct combinative multiplication of individual variable functions. Reasonable comparison is obtained between developed CLS models and experimental test results. Abstract: Onshore pipelines are generally required to transport various hydrocarbon fluids and other liquid consumables over considerably long distances. In many cases, pipe segments are unavoidably installed across geotechnically unstable environments, making them prone to significant ground deformation-induced stresses and strains which may lead to local buckling or pipe wrinkling, and possible rupture of the pipe wall. Current practice idealizes the typical deformation induced in a pipeline by movement of the surrounding or supporting soil medium as a displacement-controlled loading phenomenon characterized by monotonically-increasing uniform curvature, with or without internal pressurization and/or net-section axial stress. This idealization is adopted in this study to investigate the moment vs. curvature response of unpressurized and pressurized pipelines, with no axial stress, subjected to uniform bending deformation; with a view to develop a set of constitutive design equations for predicting the critical values of the average strain, measured over a 2D (two times pipe diameter) gauge length, that coincides with the maximum attainable bending moment. The shortcomings of existing equations, which is related to inadequate characterization of the shape of the material stress–strain curve, is effectively tackled by employing a novel stress–strain model, referred to as the 'Ndubuaku model', for accurately parametrizing the shape of stress–strain curves, including curves with a distinct yield point and extended yield plateau. Other relevant parameters investigated include the D / t (diameter-to-thickness) ratio, the internal pressure, and the material grade. A parametric study, comprising about 720 numerical simulations, is implemented herein using finite element methodology. Two semi-empirical equations are developed based on a material curve classification approach that distinguishes between 'yield-plateau' stress–strain curve materials and 'round-house' stress–strain curve materials. The predictions of the developed models are compared to results of previous experiments on pipe segments subjected to uniform bending, and a good agreement is obtained.